A IMPORTÂNCIA DE INOCULANTES NO SULCO DE PLANTIO (REMUNOM, 2024)
Inoculation is an important natural phenomenon responsible for the supply of nitrogen, the nutrient needed in the largest quantities by plants. This technology is highly relevant in agricultural production. The use of inoculants is a significant method for increasing production levels in crops, related to nitrogen fixation and tolerance to water stress, while improving soil health and promoting sustainability. Within this context, the following questions arise: What is the necessity for the use of inoculants in planting? And what is the importance of this process for planting? This research aims to report on the significance of inoculants in planting furrows. It also seeks to deepen valuable insights for producers, researchers, and Other professionals in the agricultural sector who aim to optimize food production ecologically, detailing the methods used to implement this process and discussing the differences between biological inoculants and bioinputs. This article is based on a bibliographic survey conducted through a qualitative literature review, considering the relevance of the topic. In conclusion, this research shows that the use of inoculants in planting furrows brings substantial benefits and is of great importance to farmers.